The Factor Analysis and psychometric characteristics of the self-motivation scaling and the Self-Efficacy scale of the sample of the school students in the Sultanate of Oman - Alharrasi, Saif Darwish (Journal of Educational and Psychological Sciences, 2025)
This study examined the psychometric properties and factor structures of the Self-Motivation Scale (Vallerand et al., 12 items) and the Self-Efficacy Scale (Paul et al., 7 items) among 851 seventh and tenth-grade students (423 males, 428 females) across all educational regions in Oman, employing an analytical descriptive methodology. Using Cronbach’s alpha, exploratory factor analysis (EFA), and confirmatory factor analysis (CFA), both scales demonstrated excellent reliability, with alpha coefficients of 0.914 (Self-Motivation) and 0.909 (Self-Efficacy). After removing six items from the Self-Motivation Scale, factor loadings and structural modeling confirmed the construct validity (convergent and discriminant) of both scales, while the Self-Efficacy Scale retained all original items. The findings support the use of these standardized scales to assess self-motivation and self-efficacy in relation to academic achievement and other psychological and affective variables in Omani educational research.